Study on Physicochemical Properties of Edible Oils Available in Bangladeshi Local Market - Md. Sabbir Hasan; Rownok Jahan; Md. Ashraful Alam; Mst. Khodeza Khatun; Sharif M. Al-Reza (Archives of Current Research International, 2016)
Aims: The aim of this study is the qualitative evaluation of the edible oils that are used for cooking purpose in Bangladesh. Study Design: This study was designed for selecting a good quality edible oil among various edible oils available in the local market of Bangladesh. Place and Duration of Study: Sample: Sixteen brands of different oil samples were purchased from local market of Jhenidah city of Bangladesh. The research was carried out at natural product research laboratory, Dept. of Applied Chemistry & Chemical Technology, Islamic university, Kushtia, Bangladesh during June-July 2016. Methodology: The quality of edible oils was analyzed by evaluating physicochemical properties such as density, moisture content, boiling point, peroxide, acid, iodine and saponification values using standard methods. Results: In this study oils from different brand were investigated to determine the physicochemical properties like density, moisture content, boiling point, saponification value (SV), peroxide value (PV), acid value (AV) and iodine value (IV). Highest density observed in Deshi/Ghani mustard oil (0.9683 g/ml) and lowest in Mustafa soybean oil (0.901 g/ml). On the other hand, moisture content was observed in between 0.2% to 0.82%. The highest and lowest saponification value was obtained 211.4 mg KOH/g for Jui coconut oil and 158.55 mg KOH/g for Deshi/Ghani mustard oil, respectively. It was observed that Olive oil showed maximum (12.43 meq O2/kg) and Teer soybean oil showed minimum (1.01 meq O2/kg) peroxide values. Highest acid value was observed in Jui coconut oil (18.04 mg KOH/g) and lowest in Fresh soybean oil (0.36 mg KOH/g). On the contrary, highest iodine value was observed in Rupchanda soybean oil (109.96 g I2/g oil) and lowest in Jui coconut oil (6.48 g I2/g oil). Conclusion: The results will help us for selecting a good quality edible oil.